Validación de un instrumento para medir satisfacción de pacientes renales atendidos por telemedicina durante la pandemia por COVID-19 - Laos-Choy, Katya (2023)
Objective: To evaluate the validity and reliability of an instrument that measures the satisfaction of nutritional services in renal patients. Material and Methods: The study had 7 phases within which an instrument was developed that measures the satisfaction of the patients of the Renal Health Unit, attended in nutrition workshops by telemedicine, which was applied to 31 patients. Results: The global content validity had a Lawshe index equal to 0.95. The construct validity of the satisfaction questionnaire through exploratory factor analysis found 2 factors that correspond to 87.5% of the total. The reliability of the questionnaire had a Cronbach's Alpha of 0.9. Conclusions: The questionnaire that measures the satisfaction of renal patients attended by telemedicine had high content, construct, and reliability validity.